THE ENLIGHTENING MADNESS: NUKILA AMAL’S CALA IBI AS A METAFICTION THROUGH LACANIAN PSYCHOANALYSIS - Ratnaningsih, Sri Rosyana; Nurrachman, Dian (Jurnal Pembelajaran Sastra, 2022)
The similarities of literature and human unconsciousness has been proved by many analysis or interpretation over several literary works. Nowadays, a psychoanalysis over literary works is in great popularity. Even more so for the literary works which is kind of difficult to understand. Cala Ibi is a novel with form of lyrical poetry. It has a consciousness as a metafictional to represent its narration. With such a complicated development from the character, Maya, Cala Ibi represents the concept of the mirror stage. As the representation of Lacan’s conception, Cala Ibi presented a reading problem for the reader. Therefore, the reader should read Cala Ibi in the light of psychoanalysis. This paper attempt to show the main problem that caused Cala Ibi difficult to read. The aim of this paper also to explain how Lacan’s conception represented in the form of lyrical poetry. The result of the paper shows that lyrical poetry is an apt form to present the character as a chain of signification that lead the reader to know the main idea of the novel. The development of its complicated narrative has shown the reader that Cala Ibi has no beginning or end. Thus, it is a symbolization of the infinity which reflected in Maya and Maia. On the other hands, the concept of mirror stage has formed intersubjectivity as Maya identify herself to Maia and vice versa.